Exploring the synergic mechanism of Ligusticum striatum DC. and borneol in attenuating BMECs injury and maintaining tight junctions against cerebral ischaemia based on the HIF-1α/VEGF signalling pathway. (30th January 2023) - Song, Xiaoxiong; Xing, Wanqing; Zhang, Xiaofeng; Wang, Xueqing; Ji, Jing; Lu, Jinfu; Yu, Bin; Ruan, Ming
Abstract: Ethnopharmacological relevance: Ligusticum striatum DC., also known as Ligusticum chuanxiong Hort. (LCH), is widely used in China for its excellent effect in ischaemic stroke (IS) patients, and borneol (BO) has been confirmed to maintain the blood‒brain barrier (BBB) after stroke. They are often used as a combination in the prescriptions of IS patients. Although the advantage of their combined treatment in improving brain ischaemia has been verified, their synergistic mechanism on BBB maintenance is still unclear. Aim of the study: This study was designed to evaluate the synergistic effect of maintaining the BBB between LCH and BO against IS and to further explore the potential mechanism. Materials and methods: After primary mouse brain microvascular endothelial cells (BMECs) were extracted and identified, the duration of oxygen-glucose deprivation (OGD) and the doses of LCH and BO were optimized. Then, the cells were divided into five groups: control, model, LCH, BO, and LCH + BO. Cell viability, injury degree, proliferation and migration were detected by CCK-8, LDH, EdU and wound-healing assays, respectively. Hoechst 33342 staining was adopted to detect the apoptosis rate, and western blotting was employed to observe the expressions of Bax, Bcl-2, caspase-3 and cleaved caspase-3. The TEER value and NaF permeability were measured to assess tight junction (TJ) function, while ZO-1, occludin and claudin-5 were also probed by western blotting. Moreover, the HIF-1α/VEGF pathway was observed to explore the underlying mechanism of BBB maintenance. In vivo, global cerebral ischaemia/reperfusion (GCIR) surgery was performed to establish an IS model. After treatment with LCH (200 mg/kg) and/or BO (160 mg/kg), histopathological structure and BMECs repair were observed by HE staining and immunohistochemistry of vWF. Meanwhile, TJ-associated proteins in vivo were also detected by western blotting. Results: Basically, LCH and BO had different emphases. LCH significantly attenuated the vacuolar structure, nuclear pyknosis and neuronal loss of GCIR mice, while BO focused on promoting BMECs proliferation and angiogenesis and inhibiting the degradation of TJ-associated proteins in vivo after IS. Interestingly, their combination further enhanced these effects. OGD injury markedly reduced the viability, proliferation and migration of primary BMECs; decreased the ratio of Bcl-2/Bax, TEER value, and the expressions of ZO-1, occludin and claudin-5; induced LDH release and apoptosis; and increased the cleaved caspase-3/caspase-3 ratio and NaF permeability. Meanwhile, BO might be the main contributor to the combinative treatment in ameliorating OGD-induced damage of BMECs and degradation of TJ-related proteins, and the potential mechanism might be involved in upregulating the HIF-1α/VEGF signalling pathway. Although LCH showed no obvious improvement, it could enhance the therapeutic effect of BO. Interestingly, their combination even produced some new improvements, including the reduction of cleaved caspase-3 and increase in TEER value, none of which were exhibited in their monotherapies. Conclusions: LCH and BO exhibited complementary therapeutic features in alleviating cerebral ischaemic injury by inhibiting BMECs apoptosis, maintaining the BBB and attenuating the loss of neurons. LCH preferred to protect ischaemic neurons, while BO played a key role in protecting BMECs, maintaining the BBB and TJs by activating the HIF-1α/VEGF signalling pathway. Highlights: LCH and BO exhibited synergic therapeutic effect in improving cerebral ischaemia with different mechanisms. BO played a key role in protecting BMECs, maintaining BBB and TJs by activating HIF-1α/VEGF signalling pathway. LCH preferred to protect ischaemic neurons.